The True Narration (Itinera, 2015)
Vico’s speculation is not primarily interested in a theory of myth itself, rather than in the anthropological idea laying at the core of human existence in its social and politcal forms. Hence, his mythopoeic theory must be seen as a contribution to the modern debate on subjectivity where the subject is, in the first place, author and object of the human foundational narrative.